Guide d'introduction à l'égalité de Rémunération - Oelz, Martin (Organización Internacional del Trabajo, 2013)
Ensuring that the work done by women and men is valued fairly and ending pay discrimination is essential to achieving gender equality. However, pay inequality continues to persist and gender pay gaps in some instances have stagnated or even increased.